Online Learning Information System Design Using Zachman Framework (Case Study: LMS Gajayana University Malang) - Ramadhani, Farhan; Maulanaputra, M. Farhan (International Journal of Multidisciplinary Applied and Science Research, 2025)
The development of information technology has encouraged educational institutions to adopt online learning system to improve the effectiveness and efficiency of teaching and learning process. Gajayana University Malang as one of the private universities in Indonesia has implemented Learning Management System (LMS) as a means of supporting online learning. However, to ensure that the system runs optimally and is well integrated within the institution, a comprehensive information system design is required. This research aims to design an online learning information system using the Zachman framework that is able to describe the system from various stakeholder perspectives, such as planners, owners, designers, and implementers. The research method used is case study, with data collection through observation, interview, and documentation on LMS of Gajayana University Malang. The result of this research is an online learning information system blueprint structured based on six perspectives and six focuses in Zachman Framework. This blueprint is expected to be a reference in developing and evaluating online learning systems that are more effective, efficient, and aligned with institutional needs.